Investigating Moroccan EFL 3rd Year University Students’ Critical Thinking Skills in Analysing Advertisements - Merabti, Marwa; Benmhamed, Mohamed (International Journal of Linguistics and Translation Studies, 2024)
TV commercials are ubiquitous, with people worldwide continuously exposed to various forms of commercial communication. This study aimed to assess the extent to which Moroccan university students utilize critical thinking skills when watching advertisements. Specifically, it sought to determine whether these students could analyse and evaluate the content they encounter and the impact of commercials on their purchasing behaviour. A survey was conducted with a sample of 70 third-year university students from Moulay Ismail University. Given the study’s quantitative nature, data from the survey were analysed using SPSS. The results indicated that the university students are adept critical thinkers, capable of analysing and evaluating the advertisements they viewed. A significant number of students could identify persuasive strategies employed by advertisers. Additionally, there was no notable difference between male and female students in their application of critical thinking skills; both groups could critically analyse a Maroc Telecom advertisement. Moreover, their purchasing behaviour was not influenced by viewing TV advertisements.